Pengaruh Iklan, Inovasi dan Kemajuan Teknologi terhadap Minat Beli Tiket Ferry di Pelabuhan Harbour Bay Kota Batam - Hafif, M; Purba, Tiurniari (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The increasing competition in ferry transportation services in Batam City has prompted the need for effective strategies to attract consumer interest, particularly in purchasing MV Putri Anggreni ferry tickets at Harbour Bay Port. However, existing promotional efforts have shown limitations in creativity, innovation remains stagnant, and technological adoption is underutilized. This study aims to analyze the influence of advertising, innovation, and technological advancement on consumers’ purchase intention. A quantitative descriptive method was employed, targeting residents of Batam who had previously purchased ferry tickets. From a population of 12,664 passengers recorded in March 2025, a sample of 100 respondents was selected using purposive sampling and Slovin’s formula. Data were collected through questionnaires and analyzed using SPSS 26, with tests including validity, reliability, classical assumption testing, multiple linear regression, and hypothesis testing. The results reveal that advertising contributes 12.9%, innovation 36.9%, and technological advancement 40.6% to purchase intention. The adjusted R² value of 85.9% indicates that the three variables collectively explain the majority of the variation in consumer interest. Furthermore, both partial (t-test) and simultaneous (F-test) analyses confirm that all three factors have a positive and significant effect. The study suggests enhancing digital marketing, service innovation, and user-friendly online systems to improve consumer engagement and streamline the ticket purchasing process.